Analisis Lembar Kerja Siswa Mata Pelajaran Matematika Kelas VII Ditinjau Dari Taksonomi Bloom Revisi - Kurniawan, Muhammad Fajar, Dra. Nining Setyaningsih, M.Si (2016)
Student Worksheet is a learning tool as a complement / means of supporting the implementation of the lesson plan. Student worksheet must meet at least the criteria achieved release to whether or not a basic competencies that must be mastered learners. The taxonomi bloom revision consists of knowledge dimension and the dimension of the cognitive process. This taxonomy can petrify determine how fit between objectives, assessment and learning activities.This study aimed to describe the presentation of student worksheets based on the classification and determine compatibility between basic competencies, activities and assessment at the Student Worksheet based on Bloom's Taxonomy revision This type of research is qualitative research. The subject of this study is the semester Student Worksheet prepared by MGMPs Klaten and Karanganyar. Data collection technique used documentations, observations and interviews. The validity of the data using resources. Data analysis techniques used in this research is to reduce the data, presenting data and draw conclusions. The results showed the presentation of First Instance subjects consisted of factual knowledge, conceptual and procedural with the level of cognitive processes remember, understand, and apply. Presentation of the second subject consists of factual knowledge, conceptual and procedural with the level of cognitive processes remembering, understanding, applying and analyzing. Both research subjects not comply with all of basic competencies that are taught in the second semester.